PERSEPSI DAN KEBUTUHAN SISWA PADA PENGEMBANGAN MULTIMEDIA BERBASIS ANDROID KODULAR SEBAGAI SUPLEMEN PEMBELAJARAN KOMPUTER AKUNTANSI SMK - Siti Fatimah; Fitriyanti; Beny Dwi Saputra; Yuliana FH (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2025)
Various developments in accounting computer applications can simplify the process of managing accounting information quickly and accurately. Unfortunately, there are still limitations in available learning resources. Therefore, the purpose of this study is to determine students' perceptions and needs regarding the development of Android-based multimedia Kodular as a supplement to accounting computer learning at SMK N 8 Palembang. The sample of this study was 68 students. The data collection technique used a questionnaire to obtain data on student perceptions and needs. Based on the study, the results of student perceptions of accounting computer learning that has been implemented at the school are based on aspects of perceived usefulness, perceived ease of use, response to use, social influence, and computer self efficacyhas a positive perception from students. Furthermore, 94.1% of students require creative and innovative learning resources to support computer accounting learning in schools, one of which is Kodular, an Android-based multimedia application that complements computer accounting learning in schools.